TARIAN LALAYON PADA MASYARAKAT DESA SAGEA KECAMATAN WEDA UTARA KABUPATEN HALMAHERA TENGAH - Naimuddin, Indriawati (HOLISTIK, Journal of Social and Culture, 2024)
Humans have the ability to create works of art. This is because humans have the ability of reason to form concepts and depictions of fantasy, especially those that have use value and beauty, this is the ability of creative reason. Without it, man will not be able to develop ideals and ideals, man will not be able to develop science, and create his works of art in his supporting society. One of the various art forms is dance. The existing dances have different backgrounds, according to the natural, social and cultural conditions in which they develop. For example, there are ritual dances that are sacred and religious, there are dances that are entertainment, there are dances that are social, and so on. One of them is the Lalayon dance from Sagea Village, North Weda District, Central Halmahera Regency. Lalayon dance itself is just like other folk dances, appreciating culture in general and following the norms outlined by customs, various movements reflect the subtlety of mind and character of the supporting community which is an integral part of oneself and the environment in which the dance develops which is born from ideas, activities and historical symbols. But in this day and age it is different from the past, now easy children who want to learn this dance have decreased even though there are but it is different from the previous one because there is no seriousness in playing this Lalayon dance. Only a few children in education still often learn this dance when there are district birthday events, thanksgiving events, and other major events. Keywords: lalayon dance, traditional dance, change of meaning